Comunicação direta entre dispositivos usando o modelo centrado em conteúdo - Floôr, Igor Maldonado (Universidade Federal de São Carlos, 2015)
The popularization of mobile devices capable of communicating via wireless network technologies allows us to consider different scenarios in which these devices may autonomously interact with each other. The envisioned communications would occur in a P2P fashion, as each device could simultaneously provide and consume services. A mechanism for dynamically discovering nearby devices and the available services would be necessary. Although a few existing applications already provide the direct interaction among devices they are purpose-specific and rely on pre-configured information for identifying other devices. A service-oriented architecture (SOA), based on HTTP requests and the REST or SOAP protocols, is commonly used in this type of communication. However, automatically finding available known services is still challenging. Service discovery is usually based exclusively on service name, which is not very flexible. This work proposes a new model for the direct interaction between computing devices. In an attempt to facilitate service discovery and selection we propose a content centric model in which interactions are defined according to an object’s type and the action to be applied to it. The proposed approach can workatop of existing discovery protocols, based on extensible metadata fields and on existing service data. Our proposal is evaluated according to i) the viability of direct communication between nearby devices, even when carried by users or associated to vehicles; ii) the proposed service discovery and matching using the content centric approach; iii) the effectiveness of a middleware to support the development of generic applications for direct device communication. Simulation results show our proposed model is viable. A preliminary implementation of the middleware was also evaluated and the results show that spontaneous, opportunistic, service-based interactions among devices can be achieved for different types of services.
Keywords: Arquitetura orientada a serviços; SOA; SOAP; REST; Computação ubíqua; Service oriented architecture; Device discovery; Service discovery; P2P; Middleware; Content centric communication; Ubiquitous computing; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO